Effect of Plectranthus scutellarioides (L.) Leaf Extract as Natural Antibacterial Against Staphylococcus aureus and Escherichia coli Isolated From Dairy Cattle with Subclinical Mastitis - Shafina Hanum, Farah; Witaningrum, Adiana Mutamsari; Puspitasari, Yulianna (Journal of Basic Medical Veterinary, 2022)
Mastitis is one of the causes of low milk production in dairy cows, and can be caused by bacteria such as Escherichia coli and Staphylococcus aureus. Plectranthus scutellarioides (L.) leaf has antibacterial compounds such as flavonoids, eugenol, polyphenols, steroids, tannins, and so on. The type of this research is experimental laboratory research that aims to test the antibacterial activity of the P. scutellarioides (L.) leaf extract with ethanol pro analysis as the solvent against E. coli and S. aureus bacteria isolated directly from the sample of dairy cow's milk which CMT score is (+) 3, by measuring its inhibition ability indicated by the presence of clear zone using the agar-well diffusion method. The extract concentrations tested are 5%, 10%, 20% and 40%. The result of the antibacterial test of P. scutellarioides (L.) leaf extract with ethanol p.a. as the solvent showed antibacterial activity against E. coli and S. aureus bacteria isolated directly from cow's milk samples with subclinical mastitis at certain concentrations.